Quality enhancement in Madrasa education : an exploratory study - Basheer, K. Mohammed (Cambridge Scholars Publishing, 2016)
This unique empirical study focuses on the different quality dimensions of the Madrasa education system in Kerala, southwestern India. Madrasa education is one of the largest networks of non-governmental organisations (NGOs) in the world. Despite originating several centuries ago in a vastly different social and cultural context, it continues to address the educational needs of a large section of the Muslim population in India. Although the Madrasa system has seen many significant developments over time, academia has not paid much attention to its functions, strengths and contributions. This s.